PENGARUH KETERAMPILAN ABAD 21 DAN PRAKTIK KERJA LAPANGAN (PKL) TERHADAP KESIAPAN KERJA SISWA DI SMK NEGERI 1 KARANGANYAR - Arindha Nawangsari; Mintasih Indriayu; Harini Harini (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
21st Century Skills, especially for vocational students in the field of individual life skills, must keep up with the developments and demands of the times in order to compete in the labor market. This research aims to: (1) The aims of this study were to: (1) analyze the effect of 21st century skills on students' work readiness at SMK Negeri 1 Karanganyar (2) analyze the effect of Field Work Practices on students' work readiness at SMK Negeri 1 Karanganyar (3) analyze the influence of century skills 21 and Field Work Practices together on the work readiness of students at SMK Negeri 1 Karanganyar. This research is a quantitative research. The analysis technique uses multiple linear regression. The data was processed using SPSS 25.The results showed that: (1) 21st Century Skills had a positive and significant effect on Student Work Readiness at SMK Negeri 1 Karanganyar (2) Field Work Practices had a positive and significant effect on Student Work Readiness at SMK Negeri 1 Karanganyar (3) 21st Century Skills and Field Work Practices have a joint effect on on Student Work Readiness at SMK Negeri 1 Karanganyar.